THE INFLUENCE OF THE CONSIDERATION OF FUTURE CONSEQUENCES ON LEADERSHIP EFFECTIVENESS THROUGH THE EMPOWERING LEADERSHIP OF THE EXECUTIVE TEAM AND THE TRANSFORMATIONAL LEADERSHIP OF MIDDLE MANAGEMENT - uymaz, ali (Advances in Social Sciences Research Journal, 2016)
This study aims to analyze the direct and indirect effects of the consideration of future consequences on leadership effectiveness through the empowering leadership of the executive team and the transformational leadership of middle management. The research was undertaken at a corporation that provides its managers with leadership and management training for organizational growth. A group of 330 employees participated in the study. After applying a confirmatory factor analysis to the scale used in the research, the relationships among the research variables were analyzed, using the Structural Equation Modeling (SEM). According to the results of the study, the following were determined: a) the consideration of future consequences has positive influence on leadership effectiveness through the empowering leadership of the executive team, and the transformational leadership of middle management, b) As the empowering leadership of the executive team has direct positive influence on leadership effectiveness, it also asserts indirect positive influence through the transformational leadership of middle management, c) the transformational leadership of middle management has direct positive influence on leadership effectiveness.